2003
DOI: 10.1080/08035250310009248
|View full text |Cite
|
Sign up to set email alerts
|

Skin-to-skin contact may reduce negative consequences of "the stress of being born": a study on temperature in newborn infants, subjected to different ward routines in St. Petersburg

Abstract: The results show that delivery-ward routines influence skin temperature in infants in the postnatal period. Allowing mother and baby the ward routine of skin-to-skin contact after birth may be a "natural way" of reversing stress-related effects on circulation induced during labour.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
38
0

Year Published

2005
2005
2018
2018

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 13 publications
1
38
0
Order By: Relevance
“…Our interpretation is that the skin-to-skin contact with the mother induced calmness in the infant. Bystrova et al suggested that skin-to-skin early after birth decreases the negative effects of “the stress of being born” [25]. It is likely that skin-to-skin contact with the mother even in these older infants will counteract “the stress of being forced to breastfeed”.…”
Section: Discussionmentioning
confidence: 99%
“…Our interpretation is that the skin-to-skin contact with the mother induced calmness in the infant. Bystrova et al suggested that skin-to-skin early after birth decreases the negative effects of “the stress of being born” [25]. It is likely that skin-to-skin contact with the mother even in these older infants will counteract “the stress of being forced to breastfeed”.…”
Section: Discussionmentioning
confidence: 99%
“…However traditional education materials (pictures/diagrams) explicitly instruct midwives to teach mothers to elicit the gape reflex by holding the baby away from their body then ‘quickly bring the baby to the breast’ [27,45,71-73]. This instruction may be a source of confusion to mothers, when ‘correct’ positioning and ‘correct’ attachment are emphasised in the postnatal period [7,42,74,75]. Despite revised global criteria teaching materials there remains disparity between teaching positioning and attachment in the birthing room and for subsequent breastfeeds.…”
Section: Discussionmentioning
confidence: 99%
“…The benefits of skin-to-skin contact between mother and newborn during the first hours after birth are well known [7-15]. Skin-to-skin contact between a mother and her newborn enhances both newborn feeding ability and behaviours conducive to suckling ability [16-19].…”
Section: Introductionmentioning
confidence: 99%
“…One is the duration of long-term developmental studies; another is the interference of uncontrolled factors during development and their potential resilience effects. Thus, while the impact of early care of babies and their associated experience (being separated from their mother, handled, having suckled, or not during the first hour after birth) is questioned (Klaus and Kennell, 2001) with observable short-term effects (Long et al, 1980; Jansson et al, 1995; Bystrova et al, 2003), some scarce studies on potential long-term effects indicate impacts of postpartum experience still visible in 3- or 5-year-old children (Ringler et al, 1978; Wiberg et al, 1989). …”
Section: Introductionmentioning
confidence: 99%
“…Postpartum handling may require separation from the mother at a very early stage, and intensive handling (bathing, weighting, eye ointment…) that persists even if the infant protests by crying or agitating its arms and legs (Bystrova et al, 2003). This is a typical situation when the individual has no control over the situation and this questions the possibility of its effects on later reaction modalities to stressful situations.…”
Section: Introductionmentioning
confidence: 99%